ANALISIS PENGARUH INFLASI, CADANGAN DEVISA, DAN SUKU BUNGA TERHADAP NILAI TUKAR RUPIAH TERHADAP DOLAR TAHUN 2016-2020 - Ibrahim, Muhammad Ariq; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The condition of the Rupiah exchange rate against the Dollar continued to fluctuate from 2016 to 2020. This could have an impact on the Indonesian economy. So to maintain exchange rate stability it is necessary to know what factors influence it, this study uses three economic variables to determine the relationship between the independent and dependent variables. These variables are inflation, foreign exchange reserves and interest rates. The existence of Gap Research from previous research is also the background of this research. The purpose of this study was to determine the relationship between the independent and dependent variables found in this study. The method used is the ECM method by collecting data available on BPS, Kementerian Perdagangan and Bank Indonesia websites. The results of this study are inflation and foreign exchange reserves have a negative and significant effect on the exchange rate, and interest rates have no significant effect on the exchange rate. Policies and strategies of central banks and monetary and political authorities in the world affect exchange rates which continue to fluctuate.